(untitled) (Comprehensive Journal of Science, 2025)
Today, businesses have their services in the field of public administration and interaction with citizens, not only through the internet but also via mobile devices. In this paper, we present innovative public administrations with their new business solutions and services that satisfy their users. Today, we are following the challenges of e-governance and its relationship with emerging technologies and the new service model. The development of the new concept of e-governance is intricately to a prove modification and monitoring of these modifications. To support the service, it must provide its unique service chain that is, firstly, efficient, economical, and flexible. Public administration, as distinct from state administration, comprises entities and organizations whose primary functions are not inherently executive but may assume an executive nature when carried out within legally defined frameworks. These institutions play a vital role in delivering essential services to both individuals and legal entities. Service excellence hinges on the agility with which public administrations can develop and implement innovative business solutions tailored to user needs. Incremental process improvements are insufficient in today’s dynamic environment. Consider this analogy: When urgency demands travel between cities, one would logically opt for a car or planet, a bicycle or carriage